TECHNOLOGIES OF CREATIVE THINKING OF STUDENTS IN THE PROFESSIONAL DEVELOPMENT SYSTEM AND DIRECTION TO INNOVATIVE PROFESSIONAL ACTIVITY - Musaeva Muhabbat Eshbaevna (Western European Studies, 2025)
This paper presents cutting-edge technologies for developing creative thinking among trainees in professional development programs and steering them toward innovative occupational practices using artificial intelligence (AI)
Keywords: artificial intelligence; machine learning; Duolingo